Physical characters and economics of acrylic and epoxy polymers as frame components of external skeletal fixator - SURBHI KULDEEP TYAGI; HARI PRASAD AITHAL; PRAKASH KINJAVDEKAR; AMARPAL AMARPAL; ABHIJIT MOTIRAM PAWDE; IRAWATI POLESHWAR SARODE (Indian Journal of Animal Sciences, 2014)
Physical characters of acrylic and epoxy polymers used in constructing external skeletal fixator vis-à-vis economics were compared in the present study. The fixator constructs were prepared using acrylic/epoxy polymer, 1.5 mm K-wires and ultra high density polyethylene rods as a bone substitute. Observations on fabrication ease, weight, radiographic properties and economics of polymers were taken. The epoxy polymer being doughy, less heat producing and fumeless was easier to fabricate into constructs. Hardening time for acrylic was dependent on environmental temperature with an average of 11 min; whereas, epoxy putty hardened in about 22 min and the hardening was independent of environmental temperature. Acrylic fixators were radiolucent and significantly lower in weight. Preparation cost of epoxy constructs was significantly lower than acrylic constructs. Present study provides baseline benchmarks to choose polymers in constructing external skeletal fixators according to available resources, technical expertise and economics involved.